Some Notes on Biological Aspects of Captive Javan Warty Pig (Sus verrucosus) - GONO SEMIADI; RADEN TAUFIQ PURNA NUGRAHA (Society for Indonesian Biodiversity, 2009)
The Javan warty pig (Sus verrucosus) is an endemic pig to Java and Bawean Islands, while population on Madura Island is thought to be extinct. The problem in establishing ex-situ captive breeding is the lack of information on biology or physiology. A study on these aspects was conducted in 16 Javan warty pigs and 2 cadavers in Surabaya Zoo, Surabaya. Birth profile was evaluated and blood collections were conducted, as well as analysis on spermatozoa morphology. Data showed that blood parameters were not different among the age groups (juvenile and adult) or sex and within the range of Sus scrofa. Extreme values were only obtained from the palette with the female reaching 14.5 x 103/mm3, while adult male and juvenile pigs were 58-75 x 103/mm3. Diameter of both testicles with skin intake was 56.42 mm, with the length of left testicle being 83.29 mm and right testicle 78.88 mm. Javan warty pig spermatozoa had longer size for the head and tail lengths compared to average pigs sperms. Litter size was between two to four, with the average of 2.75 litters (SD 0.98). Low litter size in this species is something that has to be concerned from the conservation point of view, therefore a captive breeding population program needs to be considered.Key words: Javan warty pig, Sus verrucosus, blood parameters, sperm